The efficacy of biomarkers in the diagnosis of acute kidney injury secondary to liver cirrhosis. Issue 14 (9th April 2021) - Yang, Yuwei; Ge, Bin; Liu, Yan; Feng, Jiafu
Abstract : Abstract: This study is to investigate the role of neutrophil gelatinase-associated lipocalin (NGAL), cystatin C (CysC) and creatinine in the diagnosis of acute kidney injury (AKI) secondary to liver cirrhosis. A total of 825 patients (including 540 liver cirrhosis patients and 285 healthy controls) were enrolled. Liver cirrhosis patients were further subdivided into AKI secondary to liver cirrhosis group (AKI group, 210 patients) and simple liver cirrhosis group (LC group, 330 patients). Serum NGAL/urine NGAL (sNGAL/uNGAL), and serum creatinine (sCr) levels as well as estimated glomerular filtration rates were measured. The diagnostic performances of these indicators in AKI secondary to liver cirrhosis were evaluated. The levels of sNGAL, uNGAL, CysC and sCr in the AKI group were significantly higher than those of LC and healthy control groups. However, the eGFR and c-aGFR of AKI group were significantly lower. With the progression of AKI (AKI-S1→AKI-S2→AKI-S3), the levels of sNGAL, uNGAL, CysC and sCr increased gradually, while the levels of c-aGFR and eGFR decreased gradually. The sNGAL, uNGAL and CysC were positively correlated with sCr (r = 0.638, 0.635, and 0.650), but negatively correlated with c-aGFR (r = -0.617, -0.606 and -0.655). However, eGFR had a negative correlation with sCr (r = -0.711), but a positive correlation with c-aGFR (r = 0.736). ROC curve analysis showed that the area under the curve for uNGAL was the largest (0.976), followed by sNGAL (0.967). The diagnostic efficacy of uNGAL and sNGAL in AKI group were 0.907 and 0.870, and the risk degrees were OR = 54.524 and 5.115, respectively. NGAL might perform better than sCr and CysC in the diagnosis of AKI secondary to liver cirrhosis, while uNGAL might be a better indicator than sNGAL in AKI diagnosis.